The Heterogeneity of Ornamental Plants in Nurseries Increases the Chance of Finding New Hosts for Phytophthora - Alejandro Soto-Plancarte; Marlene Díaz-Celaya; Gerardo Rodríguez-Alvarado; Yolanda Leticia Fernández-Pavía; Hilda Victoria Silva-Rojas; Martha Elena Pedraza-Santos; Rafael Salgado-Garciglia; Tyler Baldwin Bourret; Sylvia Patricia Fernández-Pavía (Journal of Fungi)
The production of ornamental plants in Mexico represents a job-generating activity that has grown in recent years; however, it is adversely affected by phytosanitary issues, notably those induced by Phytophthora. Studies of Phytophthora in ornamental nurseries are scarce in Mexico. The aim in this study was to identify Phytophthora species from selected ornamental plant nurseries in Mexico as potential new hosts. Samples of 13 genera diseased plant tissue and soil were collected from eight nurseries in Mexico during 2009–2010. Based on morphology and sequences of ITS rDNA, the 19 isolates obtained were identified as P. cactorum, P. capsici, P. cinnamomi, P. drechsleri, P. kelmanii, P. nicotianae, and P. tropicalis. Additional loci were sequenced to support species determinations within the P. capsici species complex; some of these isolates could not be confirmed as belonging to any described species, and one appeared to be an interspecific hybrid. This is the first report of P. kelmanii in Mexico; this is noteworthy due to being a broad host range, similar to most of the other species encountered. Evidence of nursery-grown plants serving as a Phytophthora vector to a home garden has been reported for the first time in Mexico. Cestrum nocturnum and Solanum ovigerum are new hosts for Phytophthora worldwide.